The Impact of Heating Methods on Respiratory and Allergic Diseases in Preschool Children: A Repeated Cross-Sectional Survey Across Northern and Southern China - Chenyang Wang; Shaohua Li; Yan Zhang; Haixia Zhou; Peiwen Zhang; Wei Yu (Buildings)
Indoor heating methods may influence the prevalence of respiratory and allergic diseases among preschool children. However, limited research has explored the relationship between indoor heating methods and childhood illnesses over time or on a large urban scale, and particularly the relationship between heating methods and asthma or allergic rhinitis among preschoolers from 2010 to 2019. This study conducted cross-sectional investigations in two northern cities (Taiyuan and Urumqi) and two southern cities (Chongqing and Changsha) in China during two periods: Period I (2010) and Period II (2019). Using Pearson’s chi-squared tests, we analyzed the associations between four indoor heating methods—convective heating (CH), convective and radiant heating (CH&RH), radiant heating (RH), and polluting heating (PH)—and nine respiratory and allergic diseases. Logistic regression models were employed to explore the relationships between heating methods and disease prevalence. The results revealed substantial differences in heating method choices between northern and southern Chinese cities (p < 0.001). These differences were significantly associated with the prevalence of respiratory and allergic diseases in preschoolers. Heating behaviors may have contributed to a decrease in the lifetime prevalence of asthma, pneumonia, rhinitis, and the 12-month prevalence of eczema in preschool children. In southern households, CH was linked to a lower risk of lifetime asthma (AOR: 0.63) and 12-month wheezing (AOR: 0.53). However, RH in southern households increased disease risks (AOR: 0.53). This study provides insights into the associations between heating methods and the prevalence of diseases among preschoolers across two periods in China. The findings offer new perspectives and guidance for families in selecting appropriate heating methods.